2022
DOI: 10.1186/s12958-022-00977-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of melatonin on alleviating early oxidative stress induced by DOX in mice spermatogenesis and sperm quality maintaining

Abstract: Doxorubicin (DOX) is an effective chemotherapy drug, but its clinical use has adverse effects on male reproduction. However, there are few studies about the specific biological processes related to male reproduction or strategies for improving fertility protection. In this paper, we examined the effects of DOX on spermatogenesis and sperm function, and tested the possible protective role of melatonin (MLT) against DOX’s reproductive toxicity. DOX-treated mice showed signs of significantly impaired spermatogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…The studies were published from Iran (n=11) ( 20 , 40 , 45 , 53 – 55 , 59 , 61 , 65 , 67 , 68 ), Turkey (n=9) ( 21 , 31 , 36 39 , 43 , 47 , 64 ), Egypt (n=9) ( 33 35 , 41 , 42 , 44 , 46 , 48 , 60 ), China (n=7) ( 14 , 19 , 32 , 49 , 62 , 63 , 66 ), India (n=4) ( 22 , 50 , 52 , 57 ), Thailand (n=1) ( 58 ), Nigeria (n=1) ( 56 ), and South Korea (n=1) ( 51 ). Studies employed rats (n=25) ( 20 22 , 31 , 34 37 , 39 , 41 44 , 46 48 , 51 , 56 – 58 , 61 , 62 , 64 , 65 , 68 ) and mice (n=18) ( 14 , 19 , 32 , 33 , 38 , 40 , 45 , 49 , 50 , 52 – 55 , 59 ,…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published from Iran (n=11) ( 20 , 40 , 45 , 53 – 55 , 59 , 61 , 65 , 67 , 68 ), Turkey (n=9) ( 21 , 31 , 36 39 , 43 , 47 , 64 ), Egypt (n=9) ( 33 35 , 41 , 42 , 44 , 46 , 48 , 60 ), China (n=7) ( 14 , 19 , 32 , 49 , 62 , 63 , 66 ), India (n=4) ( 22 , 50 , 52 , 57 ), Thailand (n=1) ( 58 ), Nigeria (n=1) ( 56 ), and South Korea (n=1) ( 51 ). Studies employed rats (n=25) ( 20 22 , 31 , 34 37 , 39 , 41 44 , 46 48 , 51 , 56 – 58 , 61 , 62 , 64 , 65 , 68 ) and mice (n=18) ( 14 , 19 , 32 , 33 , 38 , 40 , 45 , 49 , 50 , 52 – 55 , 59 ,…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin protects the reproductive system against the toxicity of chemotherapeutic agents (87). Zi et al reported the favorable effects of melatonin on doxorubicin-induced impaired spermatogenesis and sperm quality, except for sperm motility (88). Melatonin also suppressed bleomycin, etoposide, and cisplatin-induced testicular damage by ameliorating histopathological alterations of testes, testicular weight, and sperm motility, viability, and morphology, but not sperm count and its progressive motility (89).…”
Section: Effects On Sperm and Testis Parametersmentioning
confidence: 99%
“…Mice in the control group received an intraperitoneal injection of 100 μL normal saline (0.9% NaCl with 0.5% ethanol) daily for 35 days, while mice in the melatonin-treated group received an intraperitoneal injection of melatonin (10 mg/kg body weight, dissolved in 0.9% NaCl + 0.5% ethanol) daily for 35 days. The dosage and duration of melatonin treatment referred to our previous report (Wang et al 2022a;Zi et al 2022), and the administration of melatonin was performed at 9 am every day. On the 35th day, all mice were killed (1.25% 2,2,2-tribromoethanol sterile anesthetic, 0.2mL/kg, intraperitoneal injection), one of the testes and epididymides of each mouse were collected for fixation in Bouin's solution (HT10132, Sigma, St. Louis, MO, USA) for immunochemistry staining and microscopic evaluation, and the other testis and epididymis were collected for sperm preparation and mRNA and protein extraction.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…For full list of author affiliations and declarations see end of paper Melatonin is synthesised not only by the pineal gland, but also by reproductive organs (Huai et al 2012). It is also thought to play an important role in reproductive development and regulation (Zi et al 2022). Due to living habits, work pressure, environmental pollution and other factors, more and more men have sub-health status, and the age of marriage and child bearing is getting older (Whiteford et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation